Mahkamah Konstitusi dalam Dua Rupa: The Instigator dan Agent of Social Change - Abdul Ghoffar (Fakultas Hukum Universitas Islam Indonesia, 2017)
After more than a decade that Constitutional Court (MK) carries out its constitutional duties, this institution that was formed on 13 August 2003 has issued thousands of decisions The main problems in this research are, first, how is the role of the Constitutional Court on social change in society? Second, as a judicial institution, what kind of change model that the Constitutional Court does; is it the Instigator of Social Change or Agent of Social Change? Third, does the society prefer the role of the Constitutional Court as Instigator of Social Change or Agent of Social Change? The research method used in this research was normative-juridical research method. The results of the research concluded that, first, as a juridicial institution, the Constitutional Court has a significant role in making social changes to society. There are at least two decisions issued by the Constitutional Court that have changed public attitude, namely Decision of the Constitutional Court No 46/ PUU-VIII/2010 on